Influence of buriti pulp (Mauritia Flexuosa L.) concentration on thermophysical properties and antioxidant capacity. (November 2021) - Camelo-Silva, Callebe; Ribeiro Sanches, Marcio Augusto; Brito, Renata Moraes; Devilla, Ivano Alessandro; Tussolini, Loyse; Pertuzatti, Paula Becker
Abstract: This study aimed to determine the thermophysical properties and antioxidant capacity of buriti pulp with concentrations of 7, 9, 11, 13, and 15 °Brix. Total solids and moisture content were determined in an oven, and the specific mass was determined by the pycnometer method, while the specific heat, thermal diffusivity, and thermal conductivity were obtained using the KD2 Pro thermal properties analyzer. The antioxidant capacity was determined by the 2, 2′-azino-bis-3-ethylbenzthiazoline-6-sulfonic acid (ABTS) and 2, 2-diphenyl-1-picrylhydrazyl (DPPH) methods. At high concentrations, total solids and specific mass increased while moisture content decreased, and the soluble solids concentration did not influence specific heat, thermal diffusivity, and thermal conductivity. The antioxidant capacity of buriti pulps ranged from 0.07 to 10.45 μmol Trolox/g sample for the ABTS method and from 293.77 to 411.46 μmol Trolox/g sample for the DPPH method. Graphical abstract: Image 1 Highlights: This is the first study to provide data on the thermophysical properties of buriti pulp. Specific mass and antioxidant capacity increased with increasing concentration. The thermal properties were not affected by higher concentration. The DPPH method showed higher values of antioxidant capacity compared to ABTS. Predictive models were developed to estimate the thermophysical properties.